Household water consumption patterns in Ondo State, Nigeria (2023)
The study was conducted in Ondo State using multi-stage sampling procedure. Purposive sampling was used to select two communities while systematic random sampling was used to select 150 households with 75 respondents each from the two communities. Questionnaire and interview schedule were employed to elicit information on variables and data collected were analyzed using descriptive statistics. Majority (66.0%) were married with mean household size of 5.5 ± 2.9 members. About (41.3%) had tertiary education, less than half (37.4%) of the respondents obtained their water from well and borehole. The respondents were faced with water constraints such as water inaccessibility (1.07) and high price of water (0.40). Furthermore, water conservation strategies of the respondents include washing of used plates once a day (1.29), washing of face and foot to reduce water used for bathing (0.81), repeated wearing of clothes more than twice (0.83) and skipping bathing or ration bathing at intervals during the week (0.47). Majority (56.0%) of the respondents had favourable attitude towards sustainable water management practices and they consumed 102 litres to 162 litres of water per day. The quantity of household daily consumption of water was between 148.8 ± 61.4 litres with drinking and clothes washing being the most important activities water are used for and are used more than twice a day. Government at all levels should ensure safe sources of water for both urban and rural households and also make them available and accessible for daily consumption.